ANALISA PERBANDINGAN KINERJA KEUANGAN KABUPATEN JAYAPURA DAN KABUPATEN KEROM - Helena Lado, Meity Luisa (CV Widina Media Utama, 2022)
The 2001 Special Autonomy Law gave the regions the authority to regulate government and finance in accordance with the needs of communities. In managing finances, it is necessary to have fair, proportional, democratic, transparent and efficient financial performance. Financial performance plays an important role in determining the progress of local government development. This study aims to analyze the comparison of the financial performance of Jayapura Regency and Kerom Regency by analyzing the independence ratio, effectiveness ratio and efficiency ratio. The method used is a quantitative method by calculating the success rate of the budget design that has been determined every year in the current 4 year period. While the secondary data source is in the form of local government financial reports from 2015-2018. From the results of the study, it is known that the financial performance of Jayapura Regency has a greater level of independence than Kerom Regency. The effectiveness and efficiency value of Kerom Regency is higher than that of Jayapura Regency; the value of regional apparatus expenditure in Jayapura Regency is higher than that of Kerom Regency; and the DSCR value of Jayapura and Kerom Districts is below 1 so they are not eligible for a loan.ABSTRAKUndang-Undang Otonomi Khusus tahun 2001, memberi kewenangan kepada daerah-daerah untuk mengatur pemerintahan serta keuangan sesuai dengan kebutuhan masyarakat. Dalam mengelola keuangan diperlukan kinerja keuangan yang adil, proporsional, demokratis, transparan, dan efisien. Kinerja keuangan memegang peranan penting dalam menentukan kemajuan pembangunan pemerintahan daerah. Penelitian ini bertujuan untuk menganalisa perbandingan kinerja keuangan Kabupaten Jayapura dan Kabupaten Kerom dengan menganalisa rasio kemandirian, rasio efektifitas dan rasio efisiensi. Metode yang digunakan adalah metode kuantitatif dengan menghitung tingkat keberhasilan dari rancangan anggaran yang telah ditetapkan setiap tahun dalam periode 4 tahun berjalan. Sedangkan sumber data sekunder berupa laporan keuangan Pemerintah Daerah dari tahun 2015-2018. Dari hasil penelitian diketahui kinerja keuangan Kabupaten Jayapura memiliki tingkat kemandirian lebih besar dibandingkan Kabupaten Keerom. Nilai efektivitas dan nilai efisiensi Kabupaten Keerom lebih tinggi dibandingkan Kabupaten Jayapura; nilai belanja aparatur daerah Kabupaten Jayapura lebih tinggi dibandingkan Kabupaten Keerom; dan nilai DSCR Kabupaten Jayapura dan Keerom di bawah 1 sehingga tidak layak mendapatkan pinjaman.